Miguel Asín Palacios and theIslamic Philosophy - Guerrero, Rafael Ramón; ENNAKR, Abdelaziz (Nama Journal of Islamic Sciences and Humanities, 2023)
On the occasion of the 50th anniversary of the death of the Spanish Arabist Miguel Asín Placios, the author offers, in a brief analysis of his basic writings in this article, an overview of his contributions to the history of Islamic philosophy, especially philosophy in Andalusia.